Chapter Photocatalytic Properties of Commercially Available TiO2 Powders for Pollution Control - Nuño, Manuel (InTechOpen, 2016)
Infrared (IR) radiation comprises a beam located in the electromagnetic radiation family; it arises from the thermal vibrations of radiation that have longer wavelengths than visible light, but shorter wavelengths than microwave radiation. Its wavelength is between 750 nm and 1 mm. The amount of thermal IR radiation emitted by an object is associated with the temperature of the object, the surface area of the object and the spreading of light. IR-based technologies have been demonstrated as a method of evidence identification in forensic sciences in addition to many daily uses.